1989
DOI: 10.1103/physrevlett.62.874
|View full text |Cite
|
Sign up to set email alerts
|

Collective Band Structure and Origin of EnhancedE1Decays inO18

Abstract: The weak 4? -* it transition in ,s O was observed with a branching ratio (0.30 ±0.08)%, using the 14 C(a,/) ls O radiative-capture reaction at E a = \A4 MeV. The corresponding B(E2'Ai -* 2 3 + ) =5.7 ± 1.9 Weisskopf units appears noncollective, and serves as a crucial test of microscopic models predicting collective band structures and enhanced E\ decays in ls O; it is smaller by a factor of 3-8 than predictions of such models, and cannot be reproduced by the well-established coexistence model for ls O, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…A somewhat similar argumentation has recently been given by Gai et al [16]. On the basis of our argumentation one might also expect a stronger configuration mixing in the 0~" and 2~ states than predicted in the microscopic studies.…”
Section: Reduced E2 Transition Probabilitiessupporting
confidence: 60%
See 2 more Smart Citations
“…A somewhat similar argumentation has recently been given by Gai et al [16]. On the basis of our argumentation one might also expect a stronger configuration mixing in the 0~" and 2~ states than predicted in the microscopic studies.…”
Section: Reduced E2 Transition Probabilitiessupporting
confidence: 60%
“…We like to mention that Gai et al [16] have suggested another possible explanation for the theoretical overestimation of the B(E2,4~ ~2~) transition strength. These authors argued that the 4~ state at 4.07 MeV, which is also rather collective, mixes strongly with the 4~-state and that the various contributions to the transition matrix elements cancel noticeably.…”
Section: Reduced E2 Transition Probabilitiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The nucleus 18 O has been an important testing ground for our understanding of the clustering in N = Z nuclei. It is of importance and interest to investigate how the extra neutrons affect and enrich the clustering, since the core nucleus 16 O has the famous 12 C + α cluster states [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, mixing occurs between 2p and 4p-26 states, but that mixing can be understood [2]. Recent B(E2) measurements [4,5] cast doubt on the dominant 4p-26 assignment for the 4+ at 7.12 MeV. A new measurement and the implications are discussed in an even more recent paper [6].…”
mentioning
confidence: 98%